2018
DOI: 10.1159/000493250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Efficacy and Prognostic Factors of CLAG Treatment in Chinese Patients with Refractory or Relapsed Acute Myeloid Leukemia

Abstract: Background/Aims: The aim of this work was to investigate the efficacy and predictive factors of CLAG treatment in refractory or relapsed (R/R) acute myeloid leukemia (AML) patients. Methods: Sixty-seven R/R AML patients were enrolled in this prospective cohort study and treated by a CLAG regimen: 5 mg/m2/day cladribine (days 1–5), 2 g/m2/day cytarabine (days 1–5), and 300 μg/day filgrastim (days 0–5). The median follow-up duration was 10 months. Results: A total of 57 out of 67 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The management of post‐HCT relapsed disease is challenging. Overall response rates (ORR) with cytotoxic salvage therapy are variable, but far poorer after HCT 12‐18 . In a large registry analysis, only 15% of post‐HCT relapsed AML patients achieved a subsequent complete remission (CR); less than 5% of patients who relapsed within 6 months, and 12% of patients who relapsed 6‐24 months after HCT were alive at 3 years 18 …”
Section: Introductionmentioning
confidence: 99%
“…The management of post‐HCT relapsed disease is challenging. Overall response rates (ORR) with cytotoxic salvage therapy are variable, but far poorer after HCT 12‐18 . In a large registry analysis, only 15% of post‐HCT relapsed AML patients achieved a subsequent complete remission (CR); less than 5% of patients who relapsed within 6 months, and 12% of patients who relapsed 6‐24 months after HCT were alive at 3 years 18 …”
Section: Introductionmentioning
confidence: 99%
“…Due to the continued improvement of chemotherapeutic agents, the remission rate of leukemia has significantly improved (1)(2)(3). However, the recurrence rate remains as high as 30-40% (4).…”
Section: Introductionmentioning
confidence: 99%
“…This regimen has been demonstrated to improve the long-term survival rate from 20 to 50%; however, reinduction chemotherapy-related side effects must be acceptable to patients (27). Previous studies have reported that FLAG-IDA (granulocyte colony-stimulating factor, fludarabine, cytarabine, and idarubicin), CLAG (cladribine, cytarabine, granulocyte colony-stimulating factor), CLAM (cladribine, cytarabine, mitoxantrone) and MEC (mitoxantrone, etoposide, and cytarabine) chemotherapy regimens achieve high CR rates in patients with R/R AML (28)(29)(30)(31). However, CR rates in response to common salvage regimens decrease (10-15%) in refractory or early relapsed patients with AML (26).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported the feasibility and efficacy of FLAG-IDA chemotherapy sequential with Flu-Bu3 conditioning regimen in patients with refractory AML (34). Based on previous studies (28)(29)(30)(31) and patient characteristics, the present study selected the CLAE regimen sequential with Flu-Bu conditioning regimen for allo-HSCT in the assessed patients. Patient 1 received CLAE regimen sequential with haploid transplantation, and exhibited granulocyte deficiency at 21 after chemotherapy, the neutrophil and platelet engraftments were achieved on days 14 and 12.…”
Section: Discussionmentioning
confidence: 99%